Comparative Study of Space Configuration and Distribution in the Context of Hospitality Planning: The Case Study of Pangkor Laut Resort, Malaysia and Thanyapura Sport Hotel, Thailand - Naziri, Ahmad Faiz Hassan; Nordin, Tajul Edrus; Rashid, Kushairi (School of Social Sciences, USM, 2017)
By the year of 2020, Malaysia is expected to received 36 million of tourist that receipts RM168 billion to the country revenue. Through sport tourism, Malaysia has mobilized various international level sport events such as SEA Games 2017, Formula One and Moto GP to achieve the number. Despite the significant volumes of the market, preliminary findings are suggesting, hospitality planning in Malaysia has little concerns on the importance of space configuration and distribution to satisfy sport tourist needs. This paper is seeking to understand types of sport tourists, ideal space configurations and distribution in hospitality space planning to support sport tourism, subsequently, assess space configuration and distribution in hospitality premises in Malaysia. Using case study as the key method, the core focus of the study to: “Identify the type of sport tourists”, “Determine spatial configuration and distribution of spaces required based on sport tourist needs” and “Determine how does space of Malaysia hospitality industry compared to some established sport facilities”. Selection of case studies are carefully made considering criteria of hospitality facilities with similar spatial characteristics but vary in locality context. The study yielded better understanding on space and people interaction in the context of sport facilities, which the central to achieving an ideal spatial environment for sport tourism industry. Findings of the study suggesting space configuration and distribution for hospitality facilities in the selected case study in Malaysia are merely a resort rather a sport resort with strong traditional architecture image, thus, have great potential to become a prominent hospitality facilities based on sport tourism.